2019
DOI: 10.1002/nbm.4137
|View full text |Cite
|
Sign up to set email alerts
|

SNR optimized 31P functional MRS to detect mitochondrial and extracellular pH change during visual stimulation

Abstract: SummaryEnergy metabolism of the human visual cortex was investigated by performing 31P functional MRS.IntroductionThe human brain is known to be the main glucose demanding organ of the human body and neuronal activity can increase this energy demand. In this study we investigate whether alterations in pH during activation of the brain can be observed with MRS, focusing on the mitochondrial inorganic phosphate (Pi) pool as potential marker of energy demand.MethodsSix participants were scanned with 16 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Based on the above analysis, our results imply that the enzymes from the melatonin biosynthesis pathway, acetylserotonin O -methyltransferase in particular, are the toxicological targets for Ni(II) ions. It seems especially possible because melatonin is synthesized in mitochondria, which are known to contain pH more basic than the cytoplasm [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above analysis, our results imply that the enzymes from the melatonin biosynthesis pathway, acetylserotonin O -methyltransferase in particular, are the toxicological targets for Ni(II) ions. It seems especially possible because melatonin is synthesized in mitochondria, which are known to contain pH more basic than the cytoplasm [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cleavage is pH-dependent, and Ni(II) ions break proteins relatively slowly at pH 7.4, but much more rapidly in locations with higher pH [ 7 ]. Interestingly, pH values in the mitochondrial matrix are high enough [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] to facilitate Ni(II)-assisted hydrolysis of the peptide bond.…”
Section: Introductionmentioning
confidence: 99%
“…van de Bank et al ( 2018 ) also found no change in pH in 31 P-MRS during visual stimulation. Hendriks et al ( 2019 ) proposed a new method for measuring pH in mitochondrial or extracellular compartments during visual stimulus. Using this method, they showed a minimal shift of the downfield Pi peak toward the main Pi peak during visual stimuli, but these changes remained small and the authors recommended further validation.…”
Section: Discussionmentioning
confidence: 99%
“…As the changes in our group are minimal (yet significant) and the PCr/Pi ratio shows different behavior in the basal ganglia and occipital and temporal regions, the relevance of these changes remains unclear. Normally, energy metabolism of the brain and intracellular pH levels is controlled chiefly through a buffer process of the CO 2 /HCO 3 system, which would explain only small changes in pH detectable in 31 P‐MRS (Hendriks et al., 2019).…”
Section: Discussionmentioning
confidence: 99%